EFEKTIVITAS KINERJA OMBUDSMAN DALAM MENANGANI PENGADUAN PELAYANAN (KASUS MALADMINISTRASI DI KOTA PEKANBARU) - Putri, Kelani; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Ombudsman has a very important role in makingthe good public service because as a supervisory institution of public service provider which is according to Constitution Number 37 of 2008.Therefore the Ombudsman should emphasize on the effectiveness in overseeing public service provider. Included in implement the programs such as implementing socialization activity like introduction of the Ombudsman institution, investigation activities, monitoring and supervision of public service providers based on the issues of maladministration report. As this study aims to determine how the effectiveness and barriers of Riau Province Representative Ombudsman of the Indonesia Republic in supervision of public service provider.This research is a descriptive study that using qualitative approach as a tool of analysis. This research is conducted in the city of Pekanbaru with key informant interviews as an object of information that aims to achieve the goal to have the information. in this study. Data used in this study are primary data and secondary data obtained through direct observation and interviews with key informants.Riau Province Representative Ombudsman in dealing with complaints of maladministration had not been effective,especially in the prevention and settlement report, caused its there barriers such lack of human resources, the limited budget, the lack of facilities to support the performance of the Ombudsman of Riau Province Representative. This has an impact on the number of reports of unresolved by the ombudsman as well as the persistence of maladministration undertaken by public service provider in Pekanbaru so it is very detrimental to the public and sides related. Therefore, needs additional human resources, increasing in the funding, the addition of support facilities and needssocialization evenly related to the Riau Representative Ombudsman of the Indonesia RepublicKeywords: Effectiveness, Supervision, MaladministrationKata Kunci :Efektivitas, Pengawasan, Maladministrasi